Pengalaman dan Persepsi Driver Shopee Food Terhadap Sistem Insentif di Kota Makassar - Satriawana; Wa Ode Rayyani (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to explore the experiences and perceptions of Shopee Food drivers in Makassar City regarding the incentive system implemented by the company. Using a qualitative approach, this study involved in-depth interviews with purposively selected drivers to obtain diverse views. The data obtained were analyzed using thematic analysis techniques to identify patterns and themes that emerged from the respondents' experiences. The results showed that the incentive system had a significant impact on driver motivation and performance. Most respondents stated that financial incentives increased work enthusiasm and provided encouragement to achieve targets. However, there were also challenges faced, such as uncertainty in achieving incentives and perceptions of fairness in incentive distribution. In addition, external factors such as traffic conditions and market demand also affected their income. This study provides important insights for Shopee Food management in designing a more effective and fair incentive system, as well as improving driver welfare. These findings are expected to be a reference for further research on incentive systems in the application-based service industry.